Obestatin signalling counteracts glucocorticoid‐induced skeletal muscle atrophy via NEDD4/KLF15 axis. Issue 2 (9th March 2021) - Cid‐Díaz, Tania; Leal‐López, Saúl; Fernández‐Barreiro, Fátima; González‐Sánchez, Jessica; Santos‐Zas, Icía; Andrade‐Bulos, Luis J.; Rodríguez‐Fuentes, Manuel E.; Mosteiro, Carlos S.; Mouly, Vincent; Casabiell, Xesús; Relova, Jose Luis; Pazos, Yolanda; et al.
Abstract: Background: A therapeutic approach for the treatment of glucocorticoid‐induced skeletal muscle atrophy should be based on the knowledge of the molecular mechanisms determining the unbalance between anabolic and catabolic processes and how to re‐establish this balance. Here, we investigated whether the obestatin/GPR39 system, an autocrine signalling system acting on myogenesis and with anabolic effects on the skeletal muscle, could protect against chronic glucocorticoid‐induced muscle atrophy. Methods: In this study, we used an in vivo model of muscle atrophy induced by the synthetic glucocorticoid dexamethasone to examine the liaison molecules that define the interaction between the glucocorticoid receptor and the obestatin/GPR39 systems. The findings were extended to in vitro effects on human atrophy using human KM155C25 myotubes. Results: KLF15 and FoxO transcription factors were identified as direct targets of obestatin signalling in the control of proteostasis in skeletal muscle. The KLF15‐triggered gene expression program, including atrogenes and FoxOs, was regulated via KLF15 ubiquitination by the E3 ubiquitin ligase NEDD4. Additionally, a specific pattern of FoxO post‐translational modification, including FoxO4 phosphorylation by Akt pathway, was critical in the regulation of the ubiquitin–proteasome system. The functional cooperativity between Akt and NEDD4 in the regulation of FoxO and KLF15 provides integrated cues to counteract muscle proteostasis and re‐establish protein synthesis. Conclusions: The effective control of FoxO activity in response to glucocorticoid is critical to counteract muscle‐related pathologies. These results highlight the potential of the obestatin/GPR39 system to fine‐tune the effects of glucocorticoids on skeletal muscle wasting.